Recurrent Urinary Tract Infection in Women: Primary Care Referral Patterns in a Tertiary Care Center. Issue 2 (February 2021) - Samimi, Parisa; Ackerman, Anne Lenore; Handler, Stephanie; Eilber, Karyn S.; Anger, Jennifer
Abstract : Objectives: With more than 150 million urinary tract infections (UTIs) diagnosed globally per year, the impact on patient care is significant. We sought to examine appropriateness of management of recurrent UTI before referral to a female pelvic medicine and reconstructive surgery practice, as well as the characteristics of patients referred. Methods: The medical records of 100 consecutive women with a diagnosis of "recurrent UTI" at a single institution between November 2010 and December 2015 were reviewed. The baseline clinical characteristics, laboratory testing, and treatments before and at referral to the female pelvic medicine and reconstructive surgery were examined by descriptive statistics. Results: The evaluation and treatment patterns for recurrent UTI before specialist referral varied widely. Pelvic examination was performed in only 20.8% of patients before referral. Although most women had at least 1 culture performed (65.2%), treatments were variable. Only 42.7% of patients received recommended first-line antibiotic therapy. At symptom recurrence, only 47.2% of patients received a urine culture; most were empirically treated. Approximately 35.0% of patients received the same antibiotic upon their first recurrence. Conclusions: A large proportion of patients referred for recurrent UTI to a specialty practice had no prior culture, physical examination, or symptom-specific evaluation before referral. Despite existing guidelines, the evaluation, treatment, and referral patterns for recurrent UTI are highly varied and rarely conform to recommendations. Further studies are needed to confirm these trends and determine interventions to improve the efficacy and efficiency of primary care for women with recurrent UTI.